Advanced 3D “Modeling” and “Printing” for the Surgical Planning of a Successful Case of Thoraco-Omphalopagus Conjoined Twins Separation - Inserra, Alessandro; Borro, Luca; Spada, Marco; Frediani, Simone; Secinaro, Aurelio (Frontiers in Physiology, 2020)
Background The surgical separation of two Conjoined Twins is a particularly complex operation. Surgical times are particularly long and post-operative complications are very frequent in this type of procedure. We report a clinical case of surgical separation of two thoraco-omphalopagus conjoined twins in which, thanks to the use of (3D) three dimensional technologies, we were able to significantly reduce operative times and improve clinical outcomes. Methods We performed a 3D reconstruction of the anatomical parts involved in congenital fusion using Computer Tomography (CT) images. We obtained virtual anatomical models of the patients which allowed us to estimate essential details as the residual post-operative thoracic volume as well as the exact position of resection planes for both the general separation and for the hepatic splitting procedure. Subsequently, we printed 3D anatomical models of the thoracic cage and sternum and of the liver with the plane of resection. Finally, we printed an additional 3D anatomical model of the two patients representing different organs with multiple colors and materials. Results The use of 3D printing reduced the duration of surgery by 30% with a favorable patient outcome. Two years after the operation, the patients do not present any type of deficit and have a normal life without any significant complication. Conclusion Virtual anatomical 3D models and 3D printing represent a valid technological tool to support complex surgical operations, especially in pre-surgical planning. 3D models are important tools to better understand complex anatomy and to discuss clinical cases among members of the surgical team.